(untitled) - Goodhart, Charles A. E. (New York, N.Y., 2004)
The most successful economies have the best working financial markets. While causation obviously runs in both directions, current research has increasingly emphasized the role of finance in promoting growth. Here seven leading financial economists explore this relationship. The book seeks to answer the question of the role of finance in promoting sustainable growth and in the reduction of poverty, for example via micro-financial institutions.
Keywords: Finance,Economic development,Financial institutions; Congresses,Congresses,Congresses